A review on methods to improve the quality of recycled concrete aggregates. Issue 2 (4th March 2021) - Makul, Natt
Abstract : The need for environmental sustainability has led to the use of recycled concrete aggregates (RCAs) from structural demolition sites to produce recycled aggregate concrete (RACs) .With RACs, there is an interfacial transition zone (ITZ) between the aggregates and cement, and the ITZ may have weaker mechanical properties in RACs when compared with those in conventional concrete because of the use of RCAs. Thus, there is a need to evaluate the various methods that are suitable for improving the mechanical properties of the ITZ and RACs. This study reviews chemical-dependent treatment techniques that have been explored by various researchers. The methodology adopted in this study is an analysis of literature sources that address the quality improvement techniques and their effects on the properties of ITZ and RACs, including their compressive strength, water absorption, and their practical, economical, and environmental viability.